Botulinum toxin injections for Japanese patients with urinary incontinence caused by neurogenic detrusor overactivity: Clinical evaluation of onabotulinumtoxinA in a randomized, placebo‐controlled, double‐blind trial with an open‐label extension. (1st June 2021) - Honda, Masashi; Yokoyama, Osamu; Takahashi, Ryosuke; Matsuda, Tatsuma; Nakayama, Takashi; Mogi, Takao
Abstract : Objective: To assess the efficacy and safety of botulinum toxin treatment (onabotulinumtoxinA 200 units) for Japanese patients with neurogenic detrusor overactivity caused by spinal cord injury or multiple sclerosis. Methods: Patients with urinary incontinence refractory to pharmacological treatment were enrolled and randomized in a phase III trial. A single dose of onabotulinumtoxinA ( n  = 11) or placebo ( n  = 10) was given in the double‐blind phase, and repeat injections of onabotulinumtoxinA were given in the subsequent open‐label phase. Outcomes included urinary incontinence episodes, urodynamics, patient‐reported outcomes and adverse events. Results: The onabotulinumtoxinA group showed a numerically greater reduction in the number of urinary incontinence episodes per day than the placebo group, with the difference between the groups at week 6 of −3.02 (95% confidence interval −5.85 to −0.19). The onabotulinumtoxinA group also showed greater improvements in urodynamic assessments. Adverse events related to onabotulinumtoxinA injections were hematuria, urinary retention, urinary bladder hemorrhage, autonomic dysreflexia and epididymitis. Most events were deemed mild or moderate. Conclusions: Intradetrusor injections of onabotulinumtoxinA are efficacious and tolerable for Japanese patients with neurogenic detrusor overactivity‐related symptoms that are difficult to manage with anticholinergics and/or β3 ‐adrenergic receptor agonists.